Casa Suzana Wesley: Uma abordagem histórica do abrigo para meninas 1994 a 2003, a partir da categoria de gênero - Lima, Marilúcia Fernandes (2006)
This thesis is carried out with the intention of recognizing and bringing to light the history of Methodist women involved in social action of the church in Rio Grande do Sul, specifically in the city of Viamão. This history is portrayed through the involvement of the women who participated in this project in the activities proposed by the Suzana Wesley House between the years of 1994 and 2003 and their interrelationship with the Statute of Children and Adolescents. The concept of citizenship and diaconate is dealt with through the experiences of Methodist women and their relation with social commitment, decodified from the document Plan for the Life and Mission of the Methodist Church. The methodology used in this study is feminist critical hermeneutics, particularly the category of suspect and the analytical instrument of gender.